Clinically significant bacteria on doctors stethoscope in Makurdi, Nigeria and their antibacterial susceptibilities - Nyinoh, Iveren W.; Ackombo, Shima W. (International Journal Of Community Medicine And Public Health, 2023)
Background: The stethoscope is highly susceptible to contamination, specifically by the diaphragm that comes into contact with the patient’s body. This study aims at determining the presence of, and the most prevalent bacteria on medical interns and doctors’ stethoscopes at the federal medical centre (FMC) and Benue State university teaching hospital (BSUTH), Makurdi, assess antimicrobial susceptibility of the isolates, and compare the levels of stethoscope contamination between the hospitals. Methods: The study was a hospital-based cross-sectional study undertaken between December 2020 and May 2021. A total of 99 samples were taken using sterile swab sticks from the diaphragms of the sampled stethoscopes. Standard microbiological and biochemical tests were performed to identify the bacterial diversity. A paired sample t-test was used to compare the numbers of bacteria-contaminated stethoscopes used by doctors and interns in the two hospitals. A p<0.05 was considered as statistically significant. Results: Escherichia coli, and coagulase negative Staphylococci, were found in all of the stethoscopes tested. S. aureus was found to be the most prevalent pathogen in both hospitals (43.43%), followed by CoNS (29.29%), Klebsiella pneumonia, and Escherichia coli (both 16.16% and 11.11%) respectively. All of isolates were susceptible to the antibiotics tested. There was a significant difference in the numbers of stethoscopes contaminated from FMC (58.75, 19.31) and BSUTH (72.5, 18.52); t (3)=28.72, p=(9.27E-05), with BSUTH showing highest contamination. Conclusions: To reduce number of pathogens and risk of transmission, it is recommended that stethoscopes be sanitized after each patient consultation. Disposable stethoscope heads should also be considered to prevent cross-contamination.